2021
DOI: 10.1021/acsearthspacechem.1c00094
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Seasonal Variations in the Phase State of Secondary Organic Aerosol Material over the Contiguous US Simulated in CMAQ

Abstract: Secondary organic aerosol (SOA) accounts for a substantial portion of atmospheric particulate matter. Phase state plays an important role in the formation and evolution of SOA, while current air quality models usually assume that SOA particles are homogeneous and well-mixed liquids. In this study, we simulate glass transition temperature (T g) and particle viscosity of SOA based on organic molecular composition over the contiguous US in 2016 using the Community Multiscale Air Quality (CMAQ) model. Simulations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 111 publications
1
15
0
Order By: Relevance
“…S11), implying that organic particles would likely be solid in the FT. These results are consistent with a previous study at the site (Schum et al, 2018) and other modeling studies (Li et al, 2021;Schmedding et al, 2020;Shiraiwa et al, 2017;Shrivastava et al, 2017) indicating that organic particles in the FT are likely in solid and semisolid states. We also calculated the T g,org of organic particles at the OMP using meteorological data collected at the OMP (Table S2), and this also showed that the organics in our samples should have been in a solid state at the time they were sampled at the OMP, since the predicted T g,org is higher than the measured temperature.…”
Section: Phase State Of Particles During Long-range Transportsupporting
confidence: 93%
“…S11), implying that organic particles would likely be solid in the FT. These results are consistent with a previous study at the site (Schum et al, 2018) and other modeling studies (Li et al, 2021;Schmedding et al, 2020;Shiraiwa et al, 2017;Shrivastava et al, 2017) indicating that organic particles in the FT are likely in solid and semisolid states. We also calculated the T g,org of organic particles at the OMP using meteorological data collected at the OMP (Table S2), and this also showed that the organics in our samples should have been in a solid state at the time they were sampled at the OMP, since the predicted T g,org is higher than the measured temperature.…”
Section: Phase State Of Particles During Long-range Transportsupporting
confidence: 93%
“…131,132 In the PBL, RH and temperature will vary significantly with the time of day and season, and hence the phase state and mixing times within SOA are also expected to vary with the time of day and season. 54…”
Section: Summary Conclusion Implications and Outlookmentioning
confidence: 99%
“…Additional studies are needed to determine how the global distributions of the phase state and mixing times within SOA change with the time of day and season. The RH and temperature fields in the FT will depend less on the time of the day than at the surface. , In the PBL, RH and temperature will vary significantly with the time of day and season, and hence the phase state and mixing times within SOA are also expected to vary with the time of day and season. , …”
Section: Summary Conclusion Implications and Outlookmentioning
confidence: 99%
See 2 more Smart Citations